Effektivnost' razbega v legkoatleticeskick pryzkach - Ogandzanov, A. L.; Cesnokov, N. N. (Teorija i Praktika fiziceskoj Kul'tury, 2005)
The purpose of the research was to study the dynamics of the basic parameters of start with the growth of result in horizontal jumps and the definition of directions of its perfection, optimization of its rhythm and lengths on this basis.